Comprehensive digital training plan to strengthen tourism in rural communities of Quiroga and Membrillo, Ecuador - Agurto Asencio, Emily Isabel (2025)
This study developed a comprehensive Information and Communication Technologies (ICT) training plan to strengthen rural tourism businesses in Quiroga and Membrillo, Ecuador. A mixed-method approach was used, combining georeferenced surveys with ArcGIS Survey123, semi-structured interviews, and a systematic literature review, enabling the identification of training and structural gaps in ICT use. The results showed that over 70% of entrepreneurs face limitations in digital marketing, online payment management, and tourism promotion, as well as restricted access to technological infrastructure due to economic and geographic factors. Based on the diagnosis, a curriculum matrix was created with five sequential modules and a plan based on the 5W2H methodology, validated by experts in tourism and rural development. The proposed training model is participatory, flexible, and contextualized, articulating digital literacy, sustainability, and local governance. Community willingness to receive training and the use of social media were identified as advantages for implementing the program. Overall, the plan promotes technological appropriation, territorial competitiveness, and innovation in rural tourism. The research provides a replicable methodology for designing digital training plans in rural communities, strengthening their integration into the national tourism ecosystem.